Hyphenated study on drying kinetics and ascorbic acid degradation of guava (Psidium guajava L.) fruit. (25th February 2021) - Rokib, Sheak Nuruzzaman; Yeasmen, Nushrat; Bhuiyan, Md. Hafizur Rahman; Tasmim, Tamanna; Aziz, Mohammad Gulzarul; Alim, Md. Abdul; Islam, Md. Nazrul
Abstract: In this study, insights into the effect of process parameters (temperature: 55, 60 and 65°C; thickness: 3, 5, and 8 mm; time: up to 5 hr) on drying (mechanical, solar) kinetics and sorption behavior of guava fruits (variety: local and hybrid) with a focus on the degradation of ascorbic acid (AA) were established for the first time to the best of existing knowledge. The experimental results showed the highest moisture diffusion coefficient and lower activation energy (Ea) of 0.000326 cm 2 /s and 9.62 kcal/g.mole, respectively for hybrid mature guava variety; whereas, the highest AA degradation rate (0.107 mg AA/hr) with lower Ea (4.3 kcal/g.mole) was obtained for local mature guava variety. Besides, a mixed‐mode solar dryer assisted with a fan seemed to be efficient for drying guava fruit in comparison to drying under direct sunlight. In terms of sorption behavior, both local and hybrid guava followed sigmoidal (type II) shape isotherm where the experimental data were well fitted with Brunauer–Emmett–Teller (BET) model. Practical application: The drying conditions to have dried guava ( Psidium guajava L.) fruit with high ascorbic acid (AA) were investigated. The mathematical model was successfully applied to describe the drying kinetics and degradation of AA of guava fruit. Process parameters and methods influencing drying kinetics and AA degradation rate were detailed. BET model fits well to describe the sorption isotherms of dried guava fruit, in understanding its storage behavior. The information of this study would help in the drying process optimization of guava fruit, in order to make them available in the off‐seasons. Abstract : Drying kinetics and degradation of ascorbic acid of guava fruit were modeled. Process parameters and methods influence drying kinetics and degradation rate. BET model fits well to describe the sorption isotherms of dried guava fruit.